The Application of Sharīʿah Finance Rules in International Commercial Arbitration - Ahmad Q. Farah (Utrecht University School of Law, 2020)
Due to its flexibility, speed and confidentiality, arbitration becomes the most attractive method for contracting parties to resolve their commercial disputes. This method of choice has developed gradually in the modern legal system of Islamic Countries (ICs) over the last three decades. Thus, many of individual countries have enacted their own arbitration regulations and ratified the relevant international arbitration conventions. They also established many qualified regional arbitration institutions. Subsequently, the referral to arbitration by professionals of these countries to settle their commercial disputes gains abundant popularity. This article provides a detailed view of Sharīʿah factor in international commercial arbitration. Enforcement is certainly the goal for the arbitration process. Nevertheless, enforcement of foreign arbitral awards in the ICs could be challenged if these awards are contrary to Sharīʿah public policy. Therefore, by using this exception, the ICs can reject the enforcement of any foreign award that violates Sharīʿah public order.